Preserving Bidayuh Cultural Heritage through Collaborative Approach : Bi-Jagoi Traditional Costume - Michelle, George (Universiti Malaysia Sarawak, (UNIMAS), 2020)
Malaysia is a multi-racial country that is diverse with culture and heritage due to the existence of different groups of people. Bidayuh or the ‘Land Dayak’ is the name for several groups of indigenous people who live in Sarawak, Malaysia. The Bidayuh is famous for its unique cultural heritage which includes traditional costume, dance, crafts, beliefs, practices, and many more. However, the information on this cultural heritage is not easy to access because of the lack of accessibility to culturally related material resources. Moreover, due to urbanization, cultural heritage gradually extinct through time. To overcome those problems, Bidayuh Cultural Heritage platform will be developed to store and preserve the culture and heritage of the Bidayuh. There are three objectives of this project: to design and develop a platform to preserve the Bidayuh cultural heritage, to create implicit knowledge of Bi-Jagoi traditional costume through collaborative approach and to create a recommendation system that applies a collaborative filtering algorithm to verify the content of the Bidayuh cultural heritage before publishing the content. This work describes the development of the Bidayuh Cultural Heritage platform. This platform will provide for systematic documentation of the Bidayuh culture and heritage information, easy access as well as provide for effective information for the public.